Hyperbolic Dispersion Dominant Regime Identified through Spontaneous Emission Variations near Metamaterial Interfaces. Issue 8 (13th February 2018) - Lee, Kwang Jin; Lee, Yeon Ui; Kim, Sang Jun; André, Pascal
Abstract: Surface plasmon polariton (SPP), hyperbolic dispersion of energy and momentum, and emission interference provide opportunities to control photoluminescence properties. However, the interplays between these regimes need to be understood to take advantage of them in optoelectronic applications. Herein, broadband variations induced by hyperbolic metamaterial (HMM) multilayer nanostructures on the spontaneous emission of selected organic chromophores are investigated. Experimental and calculated spontaneous emission lifetimes are shown to vary nonmonotonously near HMM interfaces. With the HMM number of pairs used as the analysis parameter, the lifetime is shown to be independent of the number of pairs in the surface plasmon polaritons, and emission interference dominant regimes, while it decreases in the hyperbolic dispersion dominant regime. It is also shown that the spontaneous emission lifetime is similarly affected by transverse positive and transverse negative HMMs. This work has broad implications on the rational design of functional photonic surfaces to control the luminescence of semiconductor chromophores. Abstract : The spontaneous emission lifetime of organic chromophores located near hyperbolic metamaterial (HMM) multilayer nanostructures is independent of the number of pairs in the surface plasmon polaritons, and emission interference dominant regimes, while it decreases in the hyperbolic dispersion dominant regime. The spontaneous emission lifetime is similarly affected by transverse positive and transverse negative HMMs.